Economía y sociedad en APEC - Rangel Delgado, Jose Ernesto; Amparo Tello, Dagoberto; Lemus-Delgado, Daniel (Universidad de Colima, 2025)
The multiple transitions towards a post COVID-19 are considered to be the recent APEC agenda.